The emergence of a political-pedagogical teacher subjectivity: Chilean teachers’ struggle to bring pedagogy back into the political sphere - Acuña, Felipe (Education Policy Analysis Archives, 2022)
This paper analyzes the emergence of a dissident subjective position among Chilean teachers as they struggle against a new Teachers Career Policy (TCP). Since the early 1980s, comprehensive neoliberal policies have reshaped Chilean society. During this period, teachers were described as an absent subject. However, in 2014 dissident teachers spontaneously asserted themselves against a new TCP inaugurating the teachers’ spring, which in 2015 involved a 57-days strike, and again 50 days in 2019. Using the Foucauldian notion of subjective limits, I present the results of a study based on a narrative approach to understand the formation of a dissident subjectivity among Chilean teachers. I conducted 35 interviews with ten leaders and eight grassroots teachers of seven different dissident teachers’ organizations. The findings focus on analyzing political-pedagogical dissent as the central discourse mobilized by teachers to disrupt the new TCP. This discourse enables dissident teachers to clarify the current limits of their work, allowing a set of experimental practices to unfold. Finally, I discuss the emergence of a dissident teacher’s subject as a case that evokes and illustrates how new forms of political subjectivities enable us to understand the current crisis of neoliberalism experienced in Chile.